2008
DOI: 10.1016/j.metabol.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The association between insulin resistance and cytokines in adolescents: the role of weight status and exercise

Abstract: Increased adiposity is associated with insulin resistance (IR) and an inflammatory response in adults. We tested the hypotheses that cytokines associated with adiposity are also correlated with IR in early adolescents and that these relationships are moderated by weight status, levels of vigorous physical activity (VPA), or maximal aerobic power (pVO 2 max). Body mass, stature, and a fasting blood sample were obtained from 120 mid-pubertal adolescents (60 girls & 60 boys). Habitual VPA was obtained by a survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
5
50
1
1
Order By: Relevance
“…In spite of the usual positive correlation between low physical activity level and obesity 52 and risk for diabetes observed by others 53 , our results do not show an association between physical activity and nutritional status, insulin resistance or β-cell function. On the other hand, adiponectin/leptin ratio, a good parameter for disturbances on glucose homeostasis and adiposity 22,24 , was shown to be higher among active and very active adolescents, compared to sedentary and insufficiently active subjects.…”
Section: Resultscontrasting
confidence: 99%
“…In spite of the usual positive correlation between low physical activity level and obesity 52 and risk for diabetes observed by others 53 , our results do not show an association between physical activity and nutritional status, insulin resistance or β-cell function. On the other hand, adiponectin/leptin ratio, a good parameter for disturbances on glucose homeostasis and adiposity 22,24 , was shown to be higher among active and very active adolescents, compared to sedentary and insufficiently active subjects.…”
Section: Resultscontrasting
confidence: 99%
“…18 In a crosssectional analysis including 120 adolescents, higher levels of vigorous-intensity activity were associated with higher adiponectin levels. 19 A study in 60 white men and women found that RBP4 was significantly decreased in those with improved insulin sensitivity after 1 month of exercise training. 5 Similarly, in obese children, RBP4 levels were reduced remarkably after a 3-month physical activity-based lifestyle intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the relationship between the circulating levels of adipokines, anthropometric indices and cardiometabolic risk factors in obese children and adolescents (10,11). However, the majority of these have been limited mainly to associations between crude measures of adiposity such as body mass index (BMI) and CRP as a marker for an increased risk of coronary artery disease (12,13), reporting age diversity of the participants (14,15) or inconsistent results (16,17). Less is known about the presence of low-grade systemic inflammation in healthy children with central obesity and on its potential associations with various cardiometabolic alterations before the onset of puberty (18,19).…”
Section: Introductionmentioning
confidence: 99%